The Relationship Between Medication Adherence and Hypertension Status: A Cross Sectional Study in the Working Area of Tamalanrea Jaya Public Health Center Makassar City - Firman Firman; Askar Yusuf; Andi Muh Muharfian (Pakis Journal Institute, 2026)
Hypertension is a major public health problem that contributes substantially to an increased risk of cardiovascular disease and mortality. Hypertension control is strongly influenced by patients’ adherence to medication, as poor adherence may lead to uncontrolled blood pressure and increase the risk of complications. This study aimed to analyze the association between medication adherence and hypertension status among patients with hypertension in the working area of Tamalanrea Jaya Public Health Center, Makassar City. This study employed an analytical cross-sectional design. The study population consisted of all productive-age patients with hypertension aged 15–64 years who were recorded in the register book of Tamalanrea Jaya Public Health Center from January to September 2020, with an estimated population of 215 individuals. A total of 140 respondents were selected using accidental sampling. Data were analyzed using univariate and bivariate analyses, with the Chi-square test applied at a significance level of p < 0.05. The findings showed that most respondents with poor medication adherence had uncontrolled hypertension, whereas most adherent respondents had controlled hypertension. Statistical analysis revealed a significant association between medication adherence and hypertension status, with a p-value of 0.002. These findings indicate that medication adherence plays an important role in blood pressure control among patients with hypertension. Strengthening health education, routine monitoring, and the role of healthcare professionals at the primary care level is essential to support effective hypertension management.